2016
DOI: 10.1021/acsenergylett.6b00172
|View full text |Cite
|
Sign up to set email alerts
|

High Capacity of Hard Carbon Anode in Na-Ion Batteries Unlocked by POx Doping

Abstract: The capacity of hard carbon anodes in Na-ion batteries rarely reaches values beyond 300 mAh/g. We report that doping PO x into local structures of hard carbon increases its reversible capacity from 283 to 359 mAh/g. We confirm that the doped PO x is redox inactive by X-ray adsorption near edge structure measurements, thus not contributing to the higher capacity. We observe two significant changes of hard carbon's local structures caused by doping. First, the (002) d-spacing inside the turbostratic nanodomains … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
130
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 189 publications
(144 citation statements)
references
References 74 publications
11
130
1
2
Order By: Relevance
“…[55] Thus, dopings of this nature,w hich can have ad irect impact on capacity and stabilitye nhance-ments through the nanovoid regime, can be and should be implemented to desirable effect. Heteroatoms, such as N, S, and P, increase the electrode-electrolyte wettability,i na ddition to electrode conductivity enhancement through mediation in electron delocalization.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[55] Thus, dopings of this nature,w hich can have ad irect impact on capacity and stabilitye nhance-ments through the nanovoid regime, can be and should be implemented to desirable effect. Heteroatoms, such as N, S, and P, increase the electrode-electrolyte wettability,i na ddition to electrode conductivity enhancement through mediation in electron delocalization.…”
Section: Discussionmentioning
confidence: 99%
“…[49,50] The enlarged interlayer spacinga nd increased defect concentration contribute to the increase in the storage capacityt hrough the intercalation mechanism.T he major gains achievablef rom heteroatom doping strategies have been through the intercalation-deintercalation paths, which have been made facile by increasing the interlayer separations and barrierr eduction for intercalation reactions.T he defects ites developed in the hard carbon structure throughh eteroatom doping also help to improve the electrode-electrolyte interface by facilitating better wetting. [55] Nitrogen-doped hard carbon systems have been welle xplored as anode materials for SIBs. [51][52][53][54] Doping with certain groups,s uch as PO x ,i sn oted to lead to substantial enhancement in capacitive storaget hrough the sodiump ore-filling mechanism,a part from minor enhancements in intercalation capacities.…”
Section: Effect Of Heteroatom Doping On Capacitymentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that the composition [25,60] and quality [61] of the electrolyte influence strongly on the amount of charge lost for the SEI formation. Despite recent reports about tuning the porosity through PO x doping, [65] or demonstrating the correlation between pore size and capacity, [43] a deeper understanding of the mechanism of charge storage and its correlation with microstructural features appears necessary. [48] Some strategies have been successfully used to increase the coulombic efficiency by reducing the specific surface area, such as carbon coating [62,63] or the use of a graphene additive mixed with the precursor prior to pyrolysis.…”
Section: Electrochemical Performance and Optimizationmentioning
confidence: 99%